Analisis Implementasi Keselamatan,Kesehatan Kerja, dan Lingkungan (K3L) dalam Pelaksanaan Praktik Di Workshop Politeknik Gajah Tunggal - Angga Barus (Health Science Udinus, 2025)
Research conducted at the Gajah Tunggal Polytechnic aims to explore the implementation of safety, health, security and environmental (K3L) practices in mechanical engineering workshops. The results show that students have a good understanding of work safety, with 96.8% of them aware of the potential dangers that exist in the workshop environment. Even though the majority of students, namely 82.25%, use personal protective equipment (PPE) during practicum, there are still 17.75% who do not use it. However, even though awareness of safety is quite high, some students still experience accidents. This indicates the need to improve safety standards and compliance with existing procedures. Of the students who had accidents, 75.8% received medical attention, but more intensive monitoring and a quicker first aid response were needed. Furthermore, 63.1% of students carried out equipment checks before using them, which is an important step to maintain applicable safety, indicating the need for additional education to increase student compliance levels. Overall although there is a good level of awareness and compliance with safety practices, this research shows that there are gaps that need to be addressed to create a better workshop environment for students. Therefore, further efforts in education and evaluation are needed